2020
DOI: 10.3390/biom10020164
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Binding of Neuronal Calcium Sensor-1: Highly Specific Interaction with Phosphatidylinositol-3-Phosphate

Abstract: Neuronal calcium sensors are a family of N-terminally myristoylated membrane-binding proteins possessing a different intracellular localization and thereby targeting unique signaling partner(s). Apart from the myristoyl group, the membrane attachment of these proteins may be modulated by their N-terminal positively charged residues responsible for specific recognition of the membrane components. Here, we examined the interaction of neuronal calcium sensor-1 (NCS-1) with natural membranes of different lipid com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…To address alterations in these features of the protein, associated with its disulfide dimerization, we used functional assays based on components of the visual cascade, namely photoreceptor membranes/rhodopsin and rhodopsin kinase (GRK1). Indeed, NCS-1 displays a relatively high affinity towards photoreceptor membranes (comparable to those of other neuronal membranes), whereas GRK1 represents one of the structurally confirmed targets of the protein [10,54]. We found that disulfide dimerization produced a moderate negative effect on the membrane association of NCS-1 (Figure 6A).…”
Section: Functional Properties Of Dncs-1mentioning
confidence: 74%
See 2 more Smart Citations
“…To address alterations in these features of the protein, associated with its disulfide dimerization, we used functional assays based on components of the visual cascade, namely photoreceptor membranes/rhodopsin and rhodopsin kinase (GRK1). Indeed, NCS-1 displays a relatively high affinity towards photoreceptor membranes (comparable to those of other neuronal membranes), whereas GRK1 represents one of the structurally confirmed targets of the protein [10,54]. We found that disulfide dimerization produced a moderate negative effect on the membrane association of NCS-1 (Figure 6A).…”
Section: Functional Properties Of Dncs-1mentioning
confidence: 74%
“…Urea-washed photoreceptor (rod outer segment) membranes were prepared from frozen retinae, as previously described [110]. The binding of NCS-1 and dNCS-1 to the membranes was analyzed by equilibrium centrifugation assay, as described in [10,111], under non-reducing conditions. Membrane-bound NCS-1 was visualized by Western blotting (see below) and weight fractions of the bound proteins were quantified by densitometric analysis of the bands using GelAnalyzer.2010a software (Istvan Lazar Jr., University of Budapest, Budapest, Hungary).…”
Section: Membrane Binding Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…All these structural features govern the Ca 2+ -affinity of each NCS protein, which, taken together, covers the entire range of Ca 2+ -signals in neurons (K D values for calcium vary from 60–200 nM for GCAPs and 90 nM for NCS1 to 1.2 µM for VILIP1 and 17 µM for recoverin [ 26 , 27 , 31 , 32 , 33 ]). Besides the number of functional EF-hands and the nature of the residues in the Ca 2+ -binding loop, the affinity to calcium is determined by the energy cost of conformational changes associated with its coordination, and is affected by the presence of cellular membranes, individual phospholipids, and/or target proteins [ 22 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recoverin, the functioning of the Ca 2+ -myristoyl switch and subsequent membrane binding are affected by a number of different factors, such as proper structure and conformation of its unique N-terminal and C-terminal segments, electrostatic contacts between the protein and the membrane, phosphatidylserine content and potential of the membrane as well as the presence of zinc and redox state of the medium [ 12 , 31 , 36 , 37 , 38 , 39 ]. NCALD [ 40 ], VILIP1 [ 41 ] and VILIP3 [ 42 ] possess a similar Ca 2+ -myristoyl switch mechanism, whereas NCS-1 has its myristoyl group permanently exposed in the presence of membranes [ 28 , 43 , 44 , 45 ] and its membrane localization is predominantly governed by the interaction of the protein with specific phospholipids in the bilayer [ 46 ]. In contrast to the other NCSs, in GCAP1 the myristoyl group is not involved in membrane binding.…”
Section: Introductionmentioning
confidence: 99%